'And now I'm free': Women's empowerment and emancipation through entrepreneurship in Saudi Arabia and Sweden. Issue 7 (8th August 2018) - Alkhaled, Sophie; Berglund, Karin
ABSTRACT: Critical perspectives have called for the study of women's entrepreneurship as a route to social change. This 'social turn' claims women are empowered and/or emancipated through entrepreneurship with limited problematisation of how these interchangeably used concepts operate. Using an institutional perspective in combination with a narrative approach, we investigate women entrepreneurs' life stories on their 'road to freedom' where entrepreneurial activity enables them to 'break free' from particular gendered constraints. Through juxtaposing women's narratives in the contexts of Saudi Arabia and Sweden, the relationship between empowerment and emancipation is disentangled and (re)conceptualised. The findings distinguish between empowerment narrated as individual practices to achieve freedom for the self within institutional structures and emancipation as narrated as a wish to challenge and change structures of power and reach collative freedom. The yearning for collective emancipation propels women's stories of entrepreneurship by raising expectations for entrepreneurship as a vehicle for institutional change. Such stories may fascinate and inspire others to engage in entrepreneurial endeavours to become empowered, but whether they reach emancipation remains an empirical question to be answered. The performative dimension of entrepreneurial narratives is, however, their ability to turn emancipation into an (un)reachable object of desire, with a quest for even more individual empowerment and entrepreneurial activity, at the same time excluding other forms of human conduct as conducive for change.